Management of South American camelids in the eastern Andes of Northwestern Argentina: a comparative study of archaeological cases in the last two millennia - Enrique Moreno; Celeste Samec; Luis Manuel del Papa; Constanza Taboada; Pablo Mercolli; Rodrigo Nores; Stefanie Schirmer; Noel Amano (Frontiers in Environmental Archaeology)
Human-camelid interactions were an essential component in the everyday life of the societies that inhabited the South and Central Andes. While numerous studies have concentrated on this topic, they have primarily focused on the Puna plateaus, where camelids remain a key resource today. In contrast, the eastern Andean regions of Northwestern Argentina have been historically viewed as marginal and the presence of camelids in zooarchaeological assemblages has been often attributed to hunting or specialized pastoralist production for political and administrative centers located in the western valleys. Recent research in this area challenges and reshapes this view. This paper reassesses the presumed marginality of these regions by critically looking at zooarchaeological information including taxonomic, osteometric, age profiles and skeletal parts representation analyses from several key sites. We propose a preliminary model of camelid management in these environments, contributing to broader discussions of similar practices in non-high-Andean regions of South America.